Determinants Of Characteristics And Discomfort On Seating Posture Among Elderly Taxi Drivers: A Pilot Study Result - Yusoff, Irwan Syah Md; Majid, Ahmad Zuhairi Abdul; Tamrin, Shamsul Bahri Mohd (Human factors and Ergonomics Society Malaysia, 2016)
Purpose: Elderly taxi drivers among the whole taxi drivers are rapidly growth in Malaysia. The older taxi community may continue to serve their service even after retirement age of sixty years old. Therefore, older taxi drivers need to take specific consideration during driving activities according to ability and capability to sustain their life and minimizing injuries and avoiding accidents. Objective: This study is aimed to determine the characteristics and discomfort seating posture among elderly taxi drivers. Methodology: A pilot study was conducted with elderly taxi drivers using a self-administered questionnaire. It included questions on socio- demographic data, work characteristics and discomfort seating posture of the affected body part. Purposive method sampling used base on inclusive criteria; age 60 years old and above, self-driving taxi more than 1 year, no disabilities and driving using a national car. SPSS software used to analyse data. Results: The majority were employed by companies (59.1%) and worked more than eight hours daily (90.9%). The majority (95.5%) driving distance more than 150km per-week. More than half respondents (59.1%) having feeling back pain past 12 months. The highest feeling of discomfort on seating posture among elderly taxi drivers is at right buttock (50.0%) and left buttock is only (45.5%). At the lower back body parts indicates the highest (36.4%) discomfort on seating posture compares to other parts. Conclusions: An elderly taxi drivers potentially having MSD causes of current car seat design and the seating posture may not follow ergonomics principles. Most of the respondents had low awareness of important seating posture to improve their lifestyle and health.